2006
DOI: 10.5194/angeo-24-2227-2006
|View full text |Cite
|
Sign up to set email alerts
|

Dayside flow bursts and high-latitude reconnection when the IMF is strongly northward

Abstract: Abstract. The characteristics of dayside ionospheric convection are studied using Northern Hemispheric SuperDARN data and DMSP particle and flow observations when the interplanetary magnetic field (IMF) was strongly northward during 13:00-15:00 UT on 2 March 2002. Although IMF B x was positive, which is believed to favour Southern Hemisphere high-latitude reconnection at equinox, a four-cell convection pattern was observed and lasted for more than 1.5 h in the Northern Hemisphere. The reconnection rate derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 64 publications
1
16
0
Order By: Relevance
“…The suggestion of throat aurora being related with reconnection is also consistent with the statistical properties of throat aurora. It has been established that the ionospheric convection driven by reconnections generally shows two‐cell or four‐cell patterns and the convection throat gate shifts from MLN toward dawn and dusk under positive and negative IMF B y conditions [ Hu et al, ; Lockwood and Moen , ; Ruohoniemi and Greenwald , ; Weimer , ]. Compared with the SuperDARN observations, we confirmed that the orientation of throat aurora is convection aligned, so the local time distribution of the S‐N throat aurora shown in Figure can be regarded as the distribution of the center of the throat gate of the ionospheric convection near MLN.…”
Section: Summary and Discussionsupporting
confidence: 72%
“…The suggestion of throat aurora being related with reconnection is also consistent with the statistical properties of throat aurora. It has been established that the ionospheric convection driven by reconnections generally shows two‐cell or four‐cell patterns and the convection throat gate shifts from MLN toward dawn and dusk under positive and negative IMF B y conditions [ Hu et al, ; Lockwood and Moen , ; Ruohoniemi and Greenwald , ; Weimer , ]. Compared with the SuperDARN observations, we confirmed that the orientation of throat aurora is convection aligned, so the local time distribution of the S‐N throat aurora shown in Figure can be regarded as the distribution of the center of the throat gate of the ionospheric convection near MLN.…”
Section: Summary and Discussionsupporting
confidence: 72%
“…Therefore, the presence of a four convection cells pattern in this event is a strong consistent evidence for the occurrence of lobe reconnection along the highlatitude magnetopause tailward of the cusp after the Fig. 9 Two-dimensional ionospheric convection pattern derived from the SuperDARN radars at 09:24-09:26 UT shock arrival (Crooker 1992;Hu et al 2006;Lu et al 2011). In other words, the intensified and equatorwardmoving discrete auroral filaments that we observe are the typical optical feature that can be attributed to lobe reconnection occurring along the high-latitude magnetopause during shock compression.…”
Section: Resultsmentioning
confidence: 62%
“…Indeed, the reversed two‐cell convection configuration is often found in the Summer Hemisphere, whereas weak, distorted, convection is typically seen in the Winter Hemisphere under northward IMF [e.g., Bythrow et al , 1985; Knipp et al , 1993; Lu et al , 1994]. Sunward plasma flows have been observed in the Northern and Southern Hemispheres under northward IMF conditions [ Reiff, 1982; Cumnock et al , 1995; Imber et al , 2006; Hu et al , 2006]. However, the reversed two‐cell convection patterns that form simultaneously in both the hemispheres have rarely been reported partly because of the fortuitous seasonal and IMF conditions that are required for such events and partly because of the inadequate global coverage of observations.…”
Section: Introductionmentioning
confidence: 99%